Janus particles: recent advances in the biomedical applications - Le TC (Dove Medical Press, 2019)
Tu C Le,1 Jiali Zhai,2 Wei-Hsun Chiu,3 Phong A Tran,3,4 Nhiem Tran21School of Engineering, RMIT University, Melbourne, VIC 3001, Australia; 2School of Science, RMIT University, Melbourne, VIC 3001, Australia; 3School of Chemistry, Physics and Mechanical Engineering, Science and Engineering Faculty, Queensland University of Technology, Brisbane, QLD 4000, Australia; 4Interface Science and Materials Engineering group, School of Chemistry, Physics and Mechanical Engineering, Queensland University of Technology, Brisbane, QLD 4000, AustraliaCorrespondence: Nhiem TranSchool of Science, RMIT University, 124 La Trobe Street, Melbourne VIC 3000, AustraliaTel +61 3 9925 2131Email Nhiem.tran@rmit.edu.auAbstract: Janus particles, which are named after the two-faced Roman god Janus, have two distinct sides with different surface features, structures, and compositions. This asymmetric structure enables the combination of different or even incompatible physical, chemical, and mechanical properties within a single particle. Much effort has been focused on the preparation of Janus particles with high homogeneity, tunable size and shape, combined functionalities, and scalability. With their unique features, Janus particles have attracted attention in a wide range of applications such as in optics, catalysis, and biomedicine. As a biomedical device, Janus particles offer opportunities to incorporate therapeutics, imaging, or sensing modalities in independent compartments of a single particle in a spatially controlled manner. This may result in synergistic actions of combined therapies and multi-level targeting not possible in isotropic systems. In this review, we summarize the latest advances in employing Janus particles as therapeutic delivery carriers, in vivo imaging probes, and biosensors. Challenges and future opportunities for these particles will also be discussed.Keywords: Janus particles, therapeutics, theranostics, imaging, sensing